MENGUAK REALITAS PRAKTIK SEDEKAH BUMI DI DESA CIASMARA KECAMATAN PAMIJAHAN KABUPATEN BOGOR - R. Atang Supriatna; Yogaprasta Adi Nugraha (Jurnal Penelitian Sosial Ilmu Komunikasi, 2020)
Agriculture is one of the important sectors that contribute to Indonesian national income. However, agricultural development currently has a tendency to increase productivity it impacts on the agricultural system which tends to make agriculture as "commodities" and reduces the position of agriculture as an spiritual activity. Mainstreaming agriculture into "commodity" has an impact on the lost of cultural infrastructure that is supporting agriculture. This study aims to (1) see the existence of Sedakah Bumiâ€ practices in Ciasmara Village, Pamijahan District, Bogor Regency (2) Transformation practices of Sedekah Bumiâ€ in Ciasmara village, Pamijahan District, Bogor Regency. This study uses a Rapid-Ethnography approach or fast ethnography, located in the village of Ciasmara, Pamijahan District, Bogor Regency from March 2019 - August 2019. This research found that in Ciasmara village there is still the practice of Sedekah Bumiâ€, but the form of the celebration is not in the form of a colossal celebration but the celebration in the form of private in the family. This form of transformation of the Sedekah Bumiâ€ emerged as a response from the respect of each component of society so as not to violate each other's main norms adopted by each group of people. Keywords: existence, preservation of agriculture, sedekah bumi